Analysis of online user discussions on Reddit associated with the transition of use between HIV PrEP therapy - Godinez, Hector; Xu, Qing; McMann, Tiana J.; Li, Jiawei; Mackey, Timothy Ken (Frontiers in Public Health, 2023)
In 2019, the U.S. Food and Drug Administration (FDA) approved emtricitabine and tenofovir alafenamide (Descovy) as another option for HIV pre-exposure prophylaxis (PrEP) prevention for high-risk adults and adolescents. With the introduction of this new PrEP, millions of current users on emtricitabine and tenofovir disoproxil fumarate (Truvada), another PrEP medication currently used to prevent HIV transmission, have options of whether to continue their current treatment regime or transition to new treatment options. The objective of this study was to conduct a descriptive analysis to characterize user-generated social media conversations on Reddit associated with FDA-approved PrEP prevention treatment options. Key themes identified were associated with perceptions, knowledge, and attitudes associated with the transition of use of different PrEP medications. Data were collected retrospectively and prospectively from the Reddit platform for posts with keywords filtered for HIV, PrEP, and FDA-approved PrEP prevention treatment from October 2020 to December 2020. We chose the Reddit platform based on prior studies that have identified PrEP user conversations and insights on access challenges for specific AIDS communities, such as gays and men who have sex with men (MSM). Reddit posts were then manually annotated using an inductive content coding approach for key themes regarding the transition of use and other emergent themes from user-generated content. Formal coding of text data was conducted with refined codes, and sub-codes created. A total of 3,120 posts were analyzed from Reddit resulting in 315 posts that were coded for PrEP and 105 posts (33.33%) specific to user discussions regarding the transition of PrEP prevention. Overall, users expressed interest in drug switching to Descovy, particularly in the context of poorer adherence or concerns about existing side effects associated with Truvada. Other major themes included discussions about the cost of Descovy, apprehension about side effects in comparison to Truvada, insurance coverage changes, and discussions about the donation of Truvada to other users after transitioning. Among these discussions, topics related to sexual minorities, including MSM, reported concerns when considering a switch in their HIV prevention regime. Understanding the changing public perception associated with the introduction of new HIV prevention is important in the context of market access, patient safety, pharmacovigilance, and health equity, particularly among high-risk populations such as MSM. Results support the use of social media from a digital pharmacovigilance perspective to better understand emerging HIV prevention, treatment, and adherence challenges experienced by patients.